2013
DOI: 10.1103/physrevd.87.073011
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino mass matrices with two equalities between the elements or cofactors

Abstract: We study the implications of the existence of two equalities between the elements or cofactors of the neutrino mass matrix. There are sixty five structures of this type for each case. Phenomenological implications for unknown parameters like the effective Majorana mass of the electron neutrino and CP-violating phases are examined for the viable cases. To illustrate how such forms of the neutrino mass matrices may be realized, we also present a simple A 4 model for one of the classes in each case. * dev5703@yah… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 64 publications
3
23
0
Order By: Relevance
“…The similarity between texture zero structures with one mass ordering and corresponding cofactor zero structures with the opposite mass ordering has earlier been noted in [31][32][33]. In [19], the strong similarities have also been noted between the texture structures with two equalities of elements and structures with two equalities of cofactors in neutrino mass matrix, with opposite mass ordering.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…The similarity between texture zero structures with one mass ordering and corresponding cofactor zero structures with the opposite mass ordering has earlier been noted in [31][32][33]. In [19], the strong similarities have also been noted between the texture structures with two equalities of elements and structures with two equalities of cofactors in neutrino mass matrix, with opposite mass ordering.…”
Section: Introductionmentioning
confidence: 61%
“…In the lack of any convincing theory, several phenomenological ideas have been proposed in the literature so as to restrict the form of neutrino mass matrix, such as some elements of neutrino mass matrix that are considered to be zero or equal [14][15][16][17][18][19][20][21] or some cofactors of neutrino mass matrix to be either zero or equal [19,[22][23][24][25][26][27]. Specifically, mass matrices with zero textures (or cofactors) have been extensively studied [14][15][16][17][18][22][23][24] due to their connections to flavor symmetries.…”
Section: Introductionmentioning
confidence: 99%
“…Besides single texture and cofactor zeros, this more general form of duality may be seen [11] in models with two texture zeros [12] or two cofactor zeros [13], in models with equal mass matrix elements or equal cofactors [14], models with μ-τ symmetry [15], and scaling models [16].…”
Section: A Duality Between Normal and Inverted Hierarchy Modelsmentioning
confidence: 99%
“…It is found that all the textures of class B of TZ as well as TC predict a near maximal neutrino atmospheric mixing θ 23 . Using the experimental constraints on the neutrino mixing angles supplemented with a large |M ee |, class B of TZ as well as TC predict near maximal atmospheric mixing angle θ 23 and Dirac-type CP-violating phase δ fixed near This feature has not been discussed in Ref. [33] while considering the indistinguishable nature of these texture structures.…”
Section: Numerical Analysismentioning
confidence: 99%
“…Recently, a non-zero and relatively large value of the last unknown mixing angle (θ 13 ) has been confirmed by a number of neutrino oscillation experiments [1][2][3][4][5] with a best fit around 9 • . Relatively large value of θ 13 has brightened the prospects for exploring the Dirac-type CP-violating phase δ in the lepton sector, determining the octant of atmospheric mixing angle (θ 23 ) and identifying neutrino mass hierarchy. However, the currently available data on neutrino masses and mixings is not enough to determine the neutrino mass matrix (M ν ) unambiguously and additional theoretical inputs such as zero textures [6][7][8][9][10][11][12], vanishing minors [13][14][15][16][17][18][19], hybrid textures [20][21][22] and equalities between elea e-mail: dev@hnbgu.ac.in; sdev@iucaa.ernet.in b e-mail: lalsingh96@yahoo.com c e-mail: raj.physics88@gmail.com ments [23] amongst others which restrict the structure of M ν become necessary for further progress.…”
Section: Introductionmentioning
confidence: 99%